The USE OF ANDROID-BASED CNC SIMULATOR MEDIA ON THE LEARNING ACHIEVEMENT OF VOCATIONAL HIGH SCHOOL - Sumardi, Tri Ma'rufiati; Estriyanto, Yuyun; Siswandari; Cahyono, Budi Tri (Indonesian Journal of Learning and Instructional Innovation, 2024)
The rapid technological advancements have significantly impacted various aspects of life, including the field of Education. Among the changes that have occurred is the replacement of conventional methods previously used with computer technology as a learning medium. An example of this transformation is the utilization of a CNC simulator, which enables students to visualize models and concepts in a tangible form. A CNC simulator is a computer program that functions as a simulator, displaying three-dimensional images and equipped with operational buttons similar to an actual CNC machine. The CNC simulator is capable of simulating the setup and operation of a CNC machine, which is the process of automating and controlling the movement of manufacturing machines using digital technology. In practical CNC learning, the use of digital tools such as simulators can provide engaging, flexible, and effective experiences, especially in enhancing learning outcomes. Therefore the objective of this paper is to reevaluate the significance of incorporating Android-based 2A CNC simulator learning media in enhancing student achievement in the productive CNC subject. The method used in this study is literature review which encompasses theories, findings, and research articles conducted by previous scholars in the field.